A Comparison between the Range of Electron and the Range of the Heavy Charged Particles in Some Human Body Tissues - Merza, Qays Kamal (American Journal of Biology and Natural Sciences, 2025)
In this research, the range and stopping power of light particles (electron) and heavy particles (P, Be4 and Ne10) that interact with three human tissues were calculated within the energy range (o.o1-1000Mev). Through the results we obtained, we found that the stopping power of light particles decreases rapidly at low energies and reaches the lowest value and then increases at high energies and the stopping power of heavy particles increases rapidly at low energies and reaches the maximum and then gradually decreases with increasing energy. The stopping power was found as a function of energy and the stopping power of incident particles was compared with each other. We found that the stopping power is directly proportional to the atomic number of the incident particle and also depends on the energy of the incident particle and the nature of the target material, and then employing the continuous slowing down approximation (CSDA) to calculate the path length (Range), and we found that the range depends on the energy of the incident particle, the density of the target material, the atomic number of the incident particle, and the atomic number of the target. It decreases with increasing atomic number of the incident particle. All equations have been programmed to present work using FORTRAN-90 and a program has been written for numerical calculations.